ACCEPTANCE OF WEB-BASED TRAINING SYSTEM AMONG PUBLIC SECTOR EMPLOYEES (Journal of Information and Communication Technology, 2014)
Applying web-based training system is highly preferable in meeting time constraints, however, its success is subject to users’ acceptance. Previous studies highlight human challenge as the most important barrier in the implementation of an ICT-based training system. Users tend to show resistance in using new technology and online approaches. They favour the traditional way such as the face-to-face method of training. This paper presents the results of a study conducted to assess the acceptance of a web-based training by public sector employees. The study applied the Unifi ed Theory of Acceptance and Use Technology (UTAUT) with the focus on three system characteristics; system flexibility, system enjoyment, and system interactivity. A total of 290 employees from the Jordanian Public Sector participated in the study. The fi ndings revealed that system fl exibility and system enjoyment have direct effects while system interactivity has an indirect effect on the employees’ intention to use the web-based training system. In addition, system flexibility is proven to have the strongest relationship to users’ intention to use the web-based training system.